2019
DOI: 10.1002/ccd.28280
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis of optimal timing of coronary intervention in non‐ST‐elevation acute coronary syndrome

Abstract: Objectives:We conducted a meta-analysis of randomized controlled trials (RCTs) to compare the efficacy and safety of early versus delayed invasive management of non-ST-elevation acute coronary syndrome (NSTE-ACS).Background: Coronary angiography is recommended for patients with NSTE-ACS, however, the optimal timing for this remains controversial.Methods: Literature search of Pubmed/MEDLINE, Cochrane Library, and Embase for all RCTs that compared early with delayed invasive approaches in treating NSTE-ACS was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Adherence to guidelines in term of decision and timing of intervention in NSTE-ACS play a key role in improving patients’ outcomes, as the highest benefit was reported in high risk patients who were treated invasively in form of absolute risk reduction in addition to decrease recurrent ischemia, subsequent rehospitalization and revascularization as well as cardiovascular death and all-cause mortality at 30-days, 12 months and 5-years follow-up [ 15 , 24 ]. Recent Meta-analysis [ 25 ] provides strong evidence regarding the highest benefit of early invasive strategy in higher risk NSTE-ACS in term of lower major adverse cardiac events and recurrent ischemic events in parallel to what was reported by VERDICT trial [ 26 ]. However, we did not observe significant differences in in-hospital outcomes according to use of invasive strategy and this can be explained by the delayed catheterization if done in high-risk patients which can partially waive its benefit or catheterizing low risk-patients who usually benefit less from intervention compared to the higher risk categories.…”
Section: Discussionmentioning
confidence: 87%
“…Adherence to guidelines in term of decision and timing of intervention in NSTE-ACS play a key role in improving patients’ outcomes, as the highest benefit was reported in high risk patients who were treated invasively in form of absolute risk reduction in addition to decrease recurrent ischemia, subsequent rehospitalization and revascularization as well as cardiovascular death and all-cause mortality at 30-days, 12 months and 5-years follow-up [ 15 , 24 ]. Recent Meta-analysis [ 25 ] provides strong evidence regarding the highest benefit of early invasive strategy in higher risk NSTE-ACS in term of lower major adverse cardiac events and recurrent ischemic events in parallel to what was reported by VERDICT trial [ 26 ]. However, we did not observe significant differences in in-hospital outcomes according to use of invasive strategy and this can be explained by the delayed catheterization if done in high-risk patients which can partially waive its benefit or catheterizing low risk-patients who usually benefit less from intervention compared to the higher risk categories.…”
Section: Discussionmentioning
confidence: 87%
“…Similarly, there was no difference in terms of mortality (4.0% vs. 4.7%; OR: 0.85; 95% CI: 0.67–1.09; P = 0.20) or MI (6.7% vs. 7.7%; OR: 0.88; 95% CI: 0.53–1.45; P = 0.62) ( 17 ). However, another meta-analysis including 14 RCTs (9,637 patients) showed that the early invasive strategy was associated with a lower incidence of MACEs than the delayed invasive strategy (RR: 0.65; 95% CI: 0.49, 0.87; P = 0.003) ( 18 ). Contradictory results were obtained from our and previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Noninvasive stress tests for inducible ischemia are recommended before an invasive strategy (Class IA) for suspected ACS with normal ECG results and stable troponin levels [42]. In patients with NSTEMI and unstable angina, a meta-analysis of randomized controlled trials found that early versus delayed invasive management (i.e., coronary angiography) was associated with a lower incidence of major adverse cardiovascular events (MACE) (relative risk (RR) 0.65, 95% confidence intervals (CI) 0.49-0.87; p = 0.003) and recurrent ischemia (RR 0.42, 95%CI 0.26-0.69; p < 0.0005) [43]. However, accessing emergent diagnostic care in ACS is often delayed due to several factors, such as suboptimal patient flow and access to appropriate technologies.…”
Section: Cad Diagnosis-challenges With Access Accuracy and Appropriat...mentioning
confidence: 99%